Implant treatment of an edentulous patient after tumour removal in the craniofacial area – case report - Rolski, Dariusz; Nieborak, Robert; Gładkowski, Jerzy; Bojczuk, Anika; Mateńko, Dariusz; Starościak, Stanisław; Mierzwińska-Nastalska, Elżbieta (Journal of Stomatology, 2015)
Squamous cell carcinoma is the most common cancer in the oral cavity. Its characteristics include multifocal growth, almost imperceptible first symptoms, and late occurrence of pain. For that reason, it is frequently diagnosed at advanced stages. The treatment of choice in this case is surgical removal, frequently supplemented by radio- and chemotherapy. The aim of the study was to provide a protocol for implant- prosthodontic rehabilitation of a patient after a partial resection of the hard and soft palate. By using four dental implants in the maxilla and two in the mandible satisfactory stability and retention was obtained for both post-operative complete upper denture with an obturator and complete lower denture. The applied treatment led to a significant improvement in the patient’s quality of life.